PULMONARY TUBERCULOSIS - A PROSPECTIVE ANALYSIS OF HEMATOLOGICAL CHANGES - Sulochana, Sonti; V, Subhashini; Srinivasan, Chitra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This study was a prospective analysis of hematological changes in pulmonary tuberculosis (TB). The objectives of this study are (1) to study the changes in different parameters of hemogram in association of sputum-positive pulmonary TB, (2) to evaluate the disease severity and patient infectivity, (3) to determine the most common type and severity of anemia in pulmonary TB patients, and (4) to count platelets in pulmonary TB patients. TB is an important communicable disease in the world and is a major public health problem in India. Hematogical abnormalities associated with TB have been completely investigated in the literature though it is a common condition in India. Methods: A total of 150 patients of acid-fast bacilli-positive cases were included, and disseminated TB, childhood TB, and patients receiving anti-TB drugs were excluded from this study. Results: Among the 150 patients, anemia was observed in 116 cases, normocytic normchromic and microcytic hypochromic picture, leukocytosis in 68 patients, thrombocytosis in 50 patients, thrombocytopenia in 5 patients, and ESR levels were elevated in more than 82% of patients. Conclusion: A complete hemogram has been demonstrated in patients with acid-fast bacilli-positive cases in the present study. Since there was a paucity of literature in the hematological changes associated with TB, this study aimed at reinforcing the fact that they can be valuable tools in monitoring pulmonary TB.